A Study to Explore the Emergence of Shadow Phenomena in Integrative Psychotherapy Training Institutes - Wilkinson, Kate (European Journal for Qualitative Research in Psychotherapy, 2007)
This article takes the reader through a process of qualitative research in which I examine the role of shadow; human predisposition to destructive and hurtful behaviours, explored from the perspective of the psychotherapy training institute. Data is collected initially via a focus group, prior to in depth interviews with senior national and international integrative psychotherapy trainers, exploring how shadow phenomena may emerge and manifest in training organisations. Phenomenological enquiry is supported with the use of interpersonal process recall (Kagan,1996) and inquiry, attunement and involvement (Erskine,1991).Data analysis begins with the grounded theory method of Strauss and Corbin (1998) from which evolves the heuristic enquiry approach of Moustakas (1990). The heuristic experience of the researcher is employed using dream analysis, a phenomenological research interview and critical reflection on all aspects of the research process.Throughout, consideration is given to the possibility that shadow phenomenon are just as much a part of the caring environment, as is the experience of healing and growth through the therapeutic relationship, to which psychotherapy training organisations allegedly aspire.It is hoped that reading this paper will stimulate practitioners to a process of self-reflection and questioning in relation to this theme and also encourage practitioner researchers in their own journey of research.“Look for your other half - Who walks always next to you And tends to be who you aren’t.” Antonio Machado